Spiritual Development:The Practical Buddhism in Kengtung - Lovichakorntikul, Petcharat (Journal of International Buddhist Studies, 2017)
People around the world are all looking for happiness. Where can we fnd the happiness and how can we reach it? It is not easy to defne the word of “happiness” and to make this meaning to be acceptable for all people since different people have different ideas of happiness. The most important part is how to measure the level of happiness that is still questionable at this present as well. We, however, can notice that most of people from developed countries who have good education fully with high technology equipment and easily connected with the whole world at the tip of their fngers coming to the oriental countries and searching for something that are missing from their lives. Some of them are fascinated with the natural beauty, and touched by generous hearts of eastern people. Moreover, they have settled down in the land of tranquility and have a peaceful life in the continent of Asia. Kengtung is one of the charismatic places for heritage tourism and ecotourism. People who travel to Kengtung can explore the lifestyle of local people including their faith, beliefs, cultures, and happiness in their everyday life related to Buddhism. They really adore and pay high respect to Buddhism and Buddhist monks. Once we go there, we can touch the true peacefulness surrounded by Kengtung people. Hence, Kengtung is the region that individual is able to practice Buddhism and attain the inner happiness in order to cultivate their personality towards a religious or spiritual desired for the better quality of life.